TRANSFORMASI SOSIAL NU BERBASIS ASWAJA - Alfiyah, Hanik Yuni (JURNAL AT-TURAS, 2015)
The lots of members of Nahdlatul Ulama, the largest social organization in Indonesia, made it as getting a considerable position in any aspect of social life. Due to its strategic position, the cadres of Nahdlatul Ulama tried to get involved with politically bargaining their existence as ummah  with its high number of quantity, but with highly qualified ones. The current cadres of Nahdlatul Ulama have strategic position in public domain with their original aim to produce the universal well being. Regardless of the quality and quantity of Nahdlatul Ulama members in the process of social maintenance and development, they take an epistemological basis on ‘doctrine’ of Ahl Al-Sunnah wa Al-Jamâ‘ah (Aswaja). On its classical terminology, Aswaja is considered as a continuous doctrine of the ancient tradition of ulama’. However, on its contemporary terminology, Aswaja is perceived as a method of thought (manhâj al-fikr) in positioning a social reality based on deeds of tawâsuth, tawâzun, tasâmuh, ‘adâlah, dan amr ma’rûf nahî munkar.